PHONOLOGICAL SYSTEM OF MODERN UZBEK LANGUAG Volume 5,issue 8,2026 August Page 5 1 E - Dushaeva Gulbahor Dekhkonovna; I. Pardayeva (International Journal of Literature and Language Studies, 2026)
The problem of phonological systems of the Uzbek literary language, the structure of vocalism of the modern Uzbek literary language is interpreted in different ways. One of the main tasks facing us is to get acquainted with the fact that the number of phonemes in the modern Uzbek literary language varies from source to source, and on this basis to identify the reasons for the different number of phonemes. One of the most pressing issues is the creation of a system for the transcription of vocalism and consonantism in the modern Uzbek literary language. The article argues that the study of the social nature of speech sounds at the phonetic-phonological level Ttil is associated with transcription problems.